Horticultural and phytomedicinal investigation of dragon fruit (Hylocereus spp.) a crop new to South Africa - du Toit, Elsa S. (University of Pretoria, 2024)
Dissertation (MSc (Agric Horticultural Sciences))--University of Pretoria, 2023.